Deradikalisasi Pendidikan Islam Berbasis Khazanah Pesantren - Irwan Masduqi (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2013)
Violence in the name of religion often happens in Indonesia. Pesantren is considered as a nest of terrorism because it has been being taught religious radicalism here. This study can be concluded that Islam is a religion of universal love (rahmatan Lil ‘Alamin). Here, it is taught education that upholds the principle of mutual respect for differences, harmony, peace, civility, and other manifestations of noble character. But the teachings of “rahmatan lil ‘Alamin” is often reduced to justify violence in the name of religion by sensible dogmatic radical groups. De-radicalization steps are needed to develop an Islamic education that is more humane.